Salt intake reduction using umami substance-incorporated food: a secondary analysis of NHANES 2017-2018 data - Shuhei Nomura; Shiori Tanaka; Akifumi Eguchi; Takayuki Kawashima; Haruyo Nakamura; Kaung Suu Lwin; Lisa Yamasaki; Daisuke Yoneoka; Yuta Tanoe; Megumi Adachi; Hitomi Hayabuchi; Shosei Koganemaru; et al. (Cambridge University Press, 2023)
Abstract Objective: Excessive salt intake raises blood pressure and increases the risk of non-communicable diseases (NCD), such as CVD, chronic kidney disease and stomach cancer. Reducing the Na content of food is an important public health measure to control the NCD. This study quantifies the amount of salt reduced by using umami substances, i.e. glutamate, inosinate and guanylate, for adults in the USA. Design: The secondary data analysis was performed using data of the US nationally representative cross-sectional dietary survey, the National Health and Nutrition Examination Survey (NHANES) 2017-2018. Per capita daily salt intake corresponding to the NHANES food groups was calculated in the four hypothetical scenarios of 0 %, 30 %, 60 % and 90 % market share of low-Na foods in the country. The salt reduction rates by using umami substances were estimated based on the previous study results. Setting: The USA Participants: 4139 individuals aged 20 years and older in the USA Results: Replacing salt with umami substances could help the US adults reduce salt intake by 7·31-13·53 % (7·50-13·61 % for women and 7·18-13·53 % for men), which is equivalent to 0·61-1·13 g/d (0·54-0·98 g/d for women and 0·69-1·30 g/d for men) without compromising the taste. Approximately, 21·21-26·04 % of the US adults could keep their salt intake below 5 g/d, the WHO's recommendation in the scenario where there is no low-Na product on the market. Conclusions: This study provides essential information that the use of umami substances as a substitute for salt may help reduce the US adults' salt intake.